Grain boundary properties of a nickel-based superalloy: Characterisation and modelling. (1st June 2018) - Alabort, E.; Barba, D.; Sulzer, S.; Lißner, M.; Petrinic, N.; Reed, R.C.
Abstract: Miniaturised tensile tests coupled with in-situ scanning electron microscopy are used to deduce the grain boundary properties of a nickel-based superalloy at 750 °C. This allows the damage initiation, evolution and failure processes to be observed directly. The significant variation in ductility – consistent with the limited number of grain boundaries being present – is rationalised using a crystal plasticity approach calibrated by experiments on single crystals loaded along the <001>, <011>, and <111> directions. Quantitative strength and toughness values for the grain boundaries are estimated using a cohesive zone method. The modelling approach is used to determine an approximation of the size of the representative volume element (RVE) needed for volume-averaged behaviour. Graphical abstract: Image 1